Characterization of a Murine Pressure Ulcer Model to Assess Efficacy of Adipose-derived Stromal Cells. Issue 3 (March 2015) - Strong, Amy L.; Bowles, Annie C.; MacCrimmon, Connor P.; Lee, Stephen J.; Frazier, Trivia P.; Katz, Adam J.; Gawronska-Kozak, Barbara; Bunnell, Bruce A.; Gimble, Jeffrey M.
<x xml:space="preserve">Abstract</x> Background: As the world's population lives longer, the number of individuals at risk for pressure ulcers will increase considerably in the coming decades. In developed countries, up to 18% of nursing home residents suffer from pressure ulcers and the resulting hospital costs can account for up to 4% of a nation's health care budget. Although full-thickness surgical skin wounds have been used as a model, preclinical rodent studies have demonstrated that repeated cycles of ischemia and reperfusion created by exposure to magnets most closely mimic the human pressure ulcer condition. Methods: This study uses in vivo and in vitro quantitative parameters to characterize the temporal kinetics and histology of pressure ulcers in young, female C57BL/6 mice exposed to 2 or 3 ischemia-reperfusion cycles. This pressure ulcer model was validated further in studies examining the efficacy of adipose-derived stromal/stem cell administration. Results: Optimal results were obtained with the 2-cycle model based on the wound size, histology, and gene expression profile of representative angiogenic and reparative messenger RNAs. When treated with adipose-derived stromal/stem cells, pressure ulcer wounds displayed a dose-dependent and significant acceleration in wound closure rates and improved tissue histology. Conclusion: These findings document the utility of this simplified preclinical model for the evaluation of novel tissue engineering and medical approaches to treat pressure ulcers in humans.